Increased risk of mental health problems after cancer during adolescence: A register‐based cohort study. Issue 12 (3rd July 2020) - Hovén, Emma; Ljung, Rickard; Ljungman, Gustaf; Ljungman, Lisa; Skoglund, Charlotte; Fransson, Emma; Wikman, Anna
Abstract: In this nationwide, register‐based study, we estimated the risk of mental health problems in 2822 individuals diagnosed with cancer in adolescence (13‐19 years). Mental health problems were assessed by psychiatric diagnoses and/or prescribed psychotropic drugs. Cox proportional hazards models estimated hazard ratio (HR) for a psychiatric diagnosis and prescription of psychotropic drug compared to a matched comparison group (n = 28 220). Estimates were adjusted for calendar period and parent characteristics (eg, history of psychiatric diagnosis, education, country of birth). We found an increased risk of a psychiatric diagnosis during the first 5 years after the cancer diagnosis (females: HR 1.23, 95% CI, 1.06‐1.44; males: HR 1.32, 95% CI, 1.11‐1.56), and at >5 years after diagnosis (females: HR 1.31, 95% CI, 1.09‐1.58, males: HR 1.45, 95% CI, 1.18‐1.77). The risk of being prescribed antidepressant (females: HR 1.54, 95% CI, 1.30‐1.84, males: HR 2.06, 95% CI, 1.66‐2.55), antipsychotic (females: HR 2.28, 95% CI, 1.56‐3.34, males: HR 3.07, 95% CI, 2.13‐4.42), anxiolytic (females: HR 1.95, 95% CI, 1.64‐2.31, males: HR 4.02, 95% CI, 3.34‐4.84) and sedative drugs (females: HR 2.24, 95% CI, 1.84‐2.72, males: HR 3.91, 95% CI, 3.23‐4.73) were higher than for comparisons during the first 5 years after diagnosis. Median age at first psychiatric diagnosis and first prescribed psychotropic drug were 18 years. In conclusion, cancer during adolescence is associated with increased risk of mental health problems that may develop in close proximity to treatment. The findings emphasize the need for comprehensive care during treatment and follow‐up. Abstract : What's new? Survivors of childhood and adolescent cancer often are at increased risk of health conditions later in life, including neurocognitive dysfunction and depression. However, the risk of developing mental health conditions specifically after cancer during adolescence is unclear. In this study, using a matched cohort design and national register data, the authors found that adolescents with cancer are at increased risk of later psychiatric diagnosis and are likely to be prescribed psychotropic drugs, including antidepressants and antipsychotics. The findings suggest that mental health problems develop early following cancer treatment, highlighting the importance of comprehensive care and follow‐up for adolescent cancer patients.